Assessment of Functional Group in Herbal Formulation Thathuviruthi Kuligai through Fourier Transform Infrared Spectroscopy - Alexander, S.; Kamaraj, D.; Sundararajan, S. (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
Background: The Thathuviruthi kuligai is an herbal preparation used for the treatment of premature ejaculation, erectile dysfunction, oligospermia, asthenozoospermia and teratozoospermia. Objective: The objective of the present study is to characterize and assess the functional groups in the medicinal preparation “Thathuviruthi kuligai”. Materials and Methods: The ingredients were collected & purified and the drug was prepared as per Siddha literature “Noigalukana siddha parigaram part-2”. Here, the drug was subjected into characterization through FT – IR analysis. Result: FT – IR characterization shows that the presence of functional groups like O-H Stretch (Alcohol), N-H Stretch (Amines), C=C Stretch (Alkene), C=O Stretch (Carbonate ions), C-F Stretch (Alkyl & Aryl Halides), NO2 Stretch (Nitro compounds), C-Cl Stretch (Alkyl & Aryl Halides), C-H Bend (Alkene) and C-I Stretch (Alkyl & Aryl Halides) which ensure the efficacy and therapeutic effect of the drug. Conclusion: This study forms the base for the pharmaceutical analysis of Thathuviruthi kuligai which will be followed by safety and efficacy studies later.
Keywords: FT–IR; Thathuviruthi kuligai; Siddha herbal formulation; Functional groups